Compensation for Land Acquisition for Public Interest Islamic Law and Agrarian Law Perspective (Case Study in the Yogyakarta International Airport Mega Project) - Turmudi, Imam (Budapest International Research and Critics University, 2021)
In general, this study examines the issue of compensation for land acquisition for the public interest in the view of Islam and Agrarian law. While empirically, this study examines the implementation of compensation for land acquisition for the public interest in the Yogyakarta International Airpot Airport project from the perspective of Islamic law and agrarian law. This type of research is library research, namely research whose main objects are library books and other literature, which are related to the title above. So this research is a qualitative research. However, this research is strengthened by research data in the field (file research). In this study, researchers tried to examine and view the law with a complete picture. And to realize it, it must always be carried out in an interdisciplinary manner, where law is a symptom of two aspects, namely normative (das sollen) and empirical (das sein). Therefore, this research is not enough to only use library research, but rather a combination of library research with research surveys in the field. Thus the approach method used is normative juridical and sociological juridical, with descriptive-qualitative research specifications. In connection with this research is empirical legal research, the data sources used are the primary data sources and secondary data sources.